قياس التوجه الريادي لدى طالبات كلية العلوم الاقتصادية والتجارية وعلوم التسيير بجامعة جيجل – الجزائر- - كعواش جمال الدين; شاطر شفيق; عمارة شريف (جامعة الوادي University Of Eloued, 2024)
تهدف الدراسة إلى التعرف على مستوى التوجه الريادي لدى طالبات السنة الثانية ماستر بكلية العلوم الاقتصادية والتجارية وعلوم التسيير بجامعة جيجل-الجزائر، ولتحقيق ذلك استخدم الباحثون المنهج الوصفي والاستبانة كأداة رئيسية لجمع البيانات، تم اختبار فرضيات الدراسة على عينة عشوائية طبقية تقدر بـ: (248) طالبة. بعد تحليل البيانات، توصلت الدراسة إلى أن المستوى الكلي للتوجه الريادي لدى الطالبات المبحوثات جاء مرتفعاً، وأن بُعد الاستباقية جاء في المرتبة الأولى بين أبعاد التوجه الريادي من حيث درجة توافره لدى الطالبات، يليه بُعد الابتكارية، وأخيراً بُعد الميل نحو المخاطرة، كما توصلت الدراسة إلى عدم وجود فروق ذات دلالة إحصائية في مستوى التوجه الريادي لدى الطالبات المبحوثات تعزى لاختلاف خصائصهن الأكاديمية والديموغرافية. في ضوء نتائج الدراسة قدم الباحثون عدد من التوصيات الهادفة إلى تنمية وتعزيز التوجه الريادي لدى طالبات الجامعة. This study aims to identify the level of entrepreneurial orientation among second-year female master's students in the faculty of economic and commercial sciences and management sciences at the University of Jijel, Algeria. To achieve this, the researchers used the descriptive approach and the questionnaire as a main tool for data collection. The study hypotheses were tested on a stratified random sample estimated of 248 female students. After analyzing the data, the study concluded that the overall level of the entrepreneurial orientation among female respondents was high, and that the pro-activeness dimension was ranked first among the dimensions of the entrepreneurial orientation in terms of the degree of its availability among the students, followed by the innovativeness dimension, and finally risk-taking tendency. The study also found that there were no statistically significant differences in the level of entrepreneurial orientation among female students, due to the differences in academic and demographic characteristics. In light of the results of the study, the researchers presented a number of recommendations aimed at developing and strengthening the entrepreneurial orientation of female university students.
Measuring the entrepreneurial orientation of female students of the Faculty of Economic and Commercial Sciences and Management Sciences at the University of Jijel- Algeria
Keywords: ريادة أعمال; توجه ريادي; طالبات؛ جامعة جيجل; Entrepreneurship; Entrepreneurial orientation; Female students; University of Jije